1994
DOI: 10.1037/0022-3514.66.1.166
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of self-esteem lability and low trait self-esteem as vulnerability factors for depression.

Abstract: Self-esteem lability (SEL), defined as daily event-related variability in state self-esteem, and low trait self-esteem (TSE) were assessed among 205 male and female undergraduates who were currently depressed (CD), previously depressed (PD), and never depressed (ND). SEL scores were derived for the effect of positive, negative, and combined events on state self-esteem over 30 days. Consistent with psychodynamic and cognitive theories, SEL was found to be a better index of depression proneness than TSE. PD Ss s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
261
1
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 277 publications
(295 citation statements)
references
References 40 publications
28
261
1
5
Order By: Relevance
“…Roberts and Monroe (1992) found that trait self-esteem was not a strong predictor of depressive symptoms 1 week after an academic stressor, whereas variability in self-esteem (standard deviation of scores across a 3-week assessment) was a significant predictor, though only for those who were initially asymptomatic. Butler et al (1994) found that both currently and previously depressed college students had higher variability than did a never-depressed group, but the two depressed groups did not differ from each other. Self-esteem variability (but not trait self-esteem) interacted with life stress to predict depression symptoms over a 5-month follow-up period.…”
Section: Self-esteem Variability and Depressionmentioning
confidence: 90%
See 4 more Smart Citations
“…Roberts and Monroe (1992) found that trait self-esteem was not a strong predictor of depressive symptoms 1 week after an academic stressor, whereas variability in self-esteem (standard deviation of scores across a 3-week assessment) was a significant predictor, though only for those who were initially asymptomatic. Butler et al (1994) found that both currently and previously depressed college students had higher variability than did a never-depressed group, but the two depressed groups did not differ from each other. Self-esteem variability (but not trait self-esteem) interacted with life stress to predict depression symptoms over a 5-month follow-up period.…”
Section: Self-esteem Variability and Depressionmentioning
confidence: 90%
“…Most studies on self-esteem variability have focused on how it interacts with life events to predict future depression (Butler et al, 1994;Roberts & Gotlib, 1997;Roberts & Kassel, 1997;Roberts & Monroe, 1992). In contrast, we examined adverse events as a predictor of self-esteem variability.…”
Section: Adverse Eventsmentioning
confidence: 99%
See 3 more Smart Citations